Materials science and technology :a comprehensive treatment /. Volume 9, Glasses and amorphous materials / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol.ed. : Jerzy Zarzycki - Zarzycki, Jerzy
Includes bibliographical references and indexes.